What pedagogical approaches best allow ELS students in lower secondary to access the science curriculum? - Beales, Mark (2018)
This study looks at the challenges faced by English Language Support (ELS) students in mainstream classes at an international school. The focus is specifically on lower secondary students in science classes, though the findings are applicable to all subjects. It is hoped that the outcomes will support ELS students to access mainstream classes more effectively and ultimately lead to improved academic standards. Quantitative and qualitative data was initially collated from questionnaires with students and teachers, and then discussed in student and teacher Focus Groups. Following this, lesson observations and document analysis of texts used in those lessons occurred. The results of this research show that there are several key challenges faced by ELS students based largely around having to simultaneously understand new content and new language. Potential solutions are discussed through new guidelines for all teachers, teachers’ increased awareness of the challenges, improved strategies to promote reading and the use of ELS students’ L1.